2021
DOI: 10.1111/pbr.12937
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating morpho‐anatomical, physio‐biochemical and molecular mechanism imparting salinity tolerance in oats (Avena sativa)

Abstract: Oat is an important cereal crop commonly used for food, feed and forage due to its high nutritional quality and beneficial effects on human health and livestock productivity (Choubey et al., 2003).In the last few decades, salinity has emerged as a major threat to crop production, as it influences the plant growth at different developmental stages. Notably, almost 80 million ha of the world's arable land is prone to salinity stress with globally 20% (45 million ha) of irrigated and 2% (32 million ha) of dry lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…had a negative effect on germination percentage and mean germination time (Daba et al, 2019). In a study conducted in Avena sativa L., it was concluded that salinity stress greatly effects parameters such as germination percentage and mean germination time (Kumar et al, 2021). Other similar studies (Melendo & Giménez, 2019;Ceritoğlu & Erman, 2020;Ku-Or et al, 2020;Székely et al, 2021) on this subject also support our results.…”
Section: Discussionsupporting
confidence: 88%
“…had a negative effect on germination percentage and mean germination time (Daba et al, 2019). In a study conducted in Avena sativa L., it was concluded that salinity stress greatly effects parameters such as germination percentage and mean germination time (Kumar et al, 2021). Other similar studies (Melendo & Giménez, 2019;Ceritoğlu & Erman, 2020;Ku-Or et al, 2020;Székely et al, 2021) on this subject also support our results.…”
Section: Discussionsupporting
confidence: 88%
“…The oat wild relatives mostly have minimal cross compatibility with A. sativa , although some primary gene pool oat species (Fig. 2) such as A. sterilis , A. byzantina and A. fatua have been extensively used in genetic investigations (Kumar 2021; Kumari et al . 2022).…”
Section: Genetic Resourcesmentioning
confidence: 99%
“…Traditional plant breeding approaches such as germplasm screening, selection (pure line, mass and pedigree methods), polyploidisation, hybridisation (inter-and intra-specific) and mutagenesis have been used extensively to improve yield, quality traits and resilience to biotic and abiotic stresses (Boczkowska et al 2015;Roy et al 2020;Chand et al 2022). However, integration of conventional breeding methods with new biotechnological tools such as molecular breeding, omics, genome editing and genetic engineering could address prevailing challenges, because biotechnological approaches are more reliable, efficient, successful and reproducible (Kumawat et al 2020;Kumar et al 2021). Such integration will increase our understanding of the genetic basis of quantitative traits and eventually increase our abilities to modify complex traits, including yield and nutritional quality.…”
mentioning
confidence: 99%
“…Oat can be cultivated in diverse soil types ranging from sandy loam to heavy clay soil (Tiwari 2010). The production and productivity of oat substantially declines under acidic, saline and alkaline soils (Bai et al 2018;Kumar et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The production and productivity of oat substantially declines under acidic, saline and alkaline soils (Bai et al . 2018; Kumar et al . 2021).…”
Section: Introductionmentioning
confidence: 99%